Creating Age-Friendly Environments in a Smart Society in China: A Policy Review - Xu, Wenqian; Zhu, Junhua; Xi, Wanyu; Cui, Jian (Taylor & Francis, 2025)
Technology is increasingly being integrated into Age-Friendly Environments (AFEs). This study explores how technology is manifested in AFE policies in China. We conducted a content analysis of 176 policies spanning seven years to identify the relationship between technology and AFEs and the characteristics of policy development. The findings indicate that technology plays a role in advancing a smart age-friendly society, particularly in terms of enhancing community support and health services and promoting social inclusion. The findings also reveal a list of policy actions and changes in collaborative leadership and strategic priorities throughout policy development. This study emphasizes the need for ongoing policy attention to technology as an integrated component of AFE policies.